A prospective interventional study to compare the efficacy of syringe suction drainage system for prevention of subcutaneous seroma formation as compared to abdominal closure without a drain - Vazifdar, Sharmeen; Gavali, Urmila G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Seroma is a sterile collection of serous fluid in the subcutaneous tissue. The incidence ranges from 15-81%.Prophylactic drainage of wounds is aimed to reduce the wound complications and thereby the associated morbidity. Obese patients are at higher risk.There is documented beneficial effect of subcutaneous drains in obese gravida patients undergoing caesarean delivery.The most common complications of cesarean section (CS) are superficial surgical site complications including sepsis, seroma formation and breakdown.The likelihood of seroma formation without drains is 7.5 times more.Hence this study was conducted to assess the efficacy of syringe suction drainage system in prevention of seroma formation in patients undergoing CS. Methods: The study was conducted in the Department of Obstetrics and Gynaecology at the Dr. Vithalrao Vikhe Patil Foundation’s Medical College and Hospital over a period of twelve months from December 2019 to December 2020. A comparative study was conducted on 100 patients who had undergone lower segment caesarean section and had a subcutaneous layer of more than 1.5 cm. We used a drainage system made of a nasogastric tube no 10 attached to a 10 cc disposable syringe creating negative pressure for 50 of those patients. Results: Out of 50 patients in whom the drain was not used 7 developed discharge from wound and 2 patients developed wound gape while only 2 patients developed discharge from wound among those who had the drain placed. Conclusion: The syringe suction drain system is an efficient and cost effective method for prevention of subcutaneous seroma in patients undergoing CS.